Overseas and home students’ perspectives towards the implementation of portfolio-based timed-writing technique in composition class - Syafei, Muh; Fajardo, Ana Cecillia; Rusiana, Rusiana; Hilal, Achmad; Montales, Cherry Love B (EduLite: Journal of English Education, Literature and Culture, 2023)
This inquiry addressed students’ perspectives towards the implementation of the Portfolio-Based Timed-Writing Technique (PBTHT) under an international transfer credit (ICT) program at Universitas Muria Kudus. It is to answer the following questions: (1) What are the overseas students’ perspectives towards the PBTHT implementation? (2) How do their perspectives compare to their home counterparts? Using narrative analysis, this study qualitatively revealed that PBTHT is a new technique for overseas students. Their perspectives show their composition strengths cover the use of proper grammar, spelling, and mutually supportive essay elements. Meanwhile, their weaknesses include the content and mechanics. Overseas and home students expressed different perspectives due to different experiences, abilities, and teaching processes in their respective countries. Both groups acknowledged that the PBTHT implementation help them with the improvement of their writing skills.